Foreign Concepts of Distance Education - T. M. Sklyarenko (Образование и наука)
The paper analyses various foreign concepts of distance education of the past and future. In spite of the considerable progress in theoretical concept developments, the distance education still lacks the required scientific basis. This retrospective analysis is aimed at systemizing the key elements of the theory and practice of education in question, and outlining the main trends. The technology of distance education is reviewed from the following standpoints: industrialization development, distance concept and communication environment. The author points out that the modern concept of distance education has been developed under the influence of the postindustrial society and differs from the preceding approaches to education (pre-industrial and industrial); from the instrument of standard mass education it turns into the individualized way of acquiring the necessary knowledge and information. The innovative information and communication technologies make it indifferent to the time and space barriers; though the distance education is more then just a new way of transmitting the content of traditional education. The author regards it as the potential alternative to the existing educational system due to its capability to assimilate the principles of modern information society and meet its requirements.